The impact of public R&D investments on patenting activity: technology transfer at the U.S. Environmental Protection Agency. Issue 5 (4th July 2019) - Link, Albert N.; Morris, Cody A.; van Hasselt, Martijn
ABSTRACT: This paper presents estimates of the impact of public R&D on patenting activity at the U.S. Environmental Protection Agency (EPA). Using a time series of public sector agency data, we estimate the per-capita R&D elasticity of new patent applications using a knowledge production function framework model that is an expanded version of what other scholars have used with private sector data. New patent applications are an important step in the technology transfer activities of a federal agency. We estimate this elasticity to be about 2.0. This elasticity value represents an initial estimate of the impact of EPA's R&D investments on its technology transfer activity.